PTU-022 Preoperative neutrophil: lymphocyte ratio does not predict post-operative complications following hepatic resection. (28th May 2012) - Western, C E; Aroori, S; Bowles, M; Stell, D
Abstract : Introduction: Neutrophil:lymphocyte ratio (NLR) is a marker of systemic inflammation and, if high, has been shown in several studies to be correlated with adverse outcome following operative intervention in many conditions. 1–3 We attempted to test this association by analysing pre-operative NLR in all patients undergoing liver resection in our unit and attempting correlation with markers of adverse outcome in the form of post-operative complications and length of inpatient stay. Methods: Our unit is a regional tertiary referral centre for hepatic surgery undertaken for both benign and malignant disease. A database of patient demographics, radiological and histological findings and blood tests for this cohort has been prospectively maintained since 2005 and the data has been retrospectively analysed for this study. A NLR of >5 was considered elevated. Results: Between 15 July 2005 and 27 September 2011, 377 hepatic resections were performed. 62% were for colorectal carcinoma metastases, 6% for other metastases, 8% for benign disease, 7% for cholangiocarcinoma, 7% for hepatocellular carcinoma, 4% for gallbladder cancer and 2% for neuroendocrine tumours. Median patient age was 65 and 56% were male. Our median NLR was 2.5. Overall morbidity was 26%. Post-operative complications seen include bile leak 8%, liver failure 1% and post-operative death 2%. There were no intra-operative deaths. Intra-operatively, 19 % of patients required an average of 3.8 units packed cell transfusion, 6% an average of 3.7 units FFP and 2% 1.5 pool platelets. When NLR was correlated against post-operative complications, there was seen to be no association (p>0.5). Median length of inpatient stay was 8 days (range 3 to 70 days). There was also no correlation demonstrable between NLR and length of inpatient stay (p=0.23). Conclusion: Preoperative NLR does not appear to be a useful predictor of post-operative outcomes in the form of complications and post-operative hospital stay in patients undergoing liver resection. Competing interests: None declared. References: 1. Bhutta H, Agha R, Wong J, et al . Neutrophil-lymphocyte ratio predicts medium-term survival following elective major vascular surgery: a cross-sectional study. Vasc Endovascular Surg 2011;45 :227–31. 2. Gomez D, Farid S, Malik HZ, et al . Preoperative neutrophil-to-lymphocyte ratio as a prognostic predictor after curative resection for hepatocellular carcinoma. World J Surg 2008;32 :1757–62. 3. Jung MR, Park YK, Jeong O, et al . Elevated preoperative neutrophil to lymphocyte ratio predicts poor survival following resection in late stage gastric cancer. J Surg Oncol 2011;104 :504–10.